Implementasi Penggunaan Fitur Tarik Tunai Tanpa Kartu ATM Melalui Aplikasi BRI Mobile pada Masyarakat di Kota Kupang - Maria Ivantri Dorwi; Reyner F. Makatita; Fransina W. Ballo (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study aims to determine the implementation of the use of the ATM cardless cash withdrawal feature through the BRI Mobile application in Kupang City and to determine the development strategy for the ATM Cardless Cash Withdrawal Feature through the BRI Mobile application in the community in Kupang City. This study uses a qualitative descriptive approach, by conducting structured interviews with informants of leaders, employees and BRI Bank customers who use the ATM cardless cash withdrawal feature through the BRI Mobile application in the community in Kupang City. The data analysis technique in this study uses SWOT analysis. The results of the study using SWOT Analysis (Strength, Weakness, Opportunities, Threat) concluded that the total IFAS score of 3.30 indicates that BRI Bank is strong internally in implementing the ATM Cardless Cash Withdrawal Feature through the BRI Mobile application. While the total EFAS score of 3.10 indicates that BRI is able to read the opportunities that come and anticipate existing threats.